Exploring definitions of consent and healthy relationships among college students with disabilities: "I think it’s fuzzy" - Anderson, Jocelyn C. (Journal of family violence, 2022)
College students with disabilities (SWDs) experience elevated rates of sexual violence and intimate partner violence compared with their non-disabled peers. While tailored interventions for these pressing health issues are needed, current research lacks investigation into how SWDs conceptualize relevant key concepts, such as consent and healthy relationships. This descriptive qualitative study explored these concepts through semi-structured interviews with college SWDs (n = 49), 18–24 years old, in Pennsylvania and West Virginia. The results culminated in six rich, descriptive themes addressing: 1) interpersonal and intrapersonal skills necessary for relationship health; 2) normalization of unhealthy treatment by a partner due to manipulation, denial, and love for the partner; 3) how dichotomous definitions of consent interfere with practical application in lived experiences; 4) how active consent can be both facilitated and hindered within the context of a romantic relationship; 5) perceptions that healthcare providers aim to elicit disclosures of abuse rather than initiate a discussion about relationship health; and 6) students' reticence to disclose abuse to healthcare providers due to mistrust and fear over loss of agency. These results contradict historic narratives that SWDs do not have the same sexual and relationship beliefs and experiences as other students and highlight the perspectives of this marginalized population. Implications for campus prevention programming and healthcare practices include incorporating intersections of disability and violence, discussing the nuances of consent and substance use, and creating conversations about relationship health that are transparent, non-judgmental, and include a broad range of types of abuse.